Penelitian Perubahan Kinerja Mesin dan Karakteristik Emisi pada Remapping ECU pada Sistem Mesin 150cc Empat Tak dengan Satu Poros Nocken Atas - Dodo Wicaksono; Alief Muhammad; Muhammad Fathuddin Noor; Indah Noor Dwi Kusuma Dewi; Mava Nurhaliza Helsinky; Dani Hari Tunggal Prasetiyo; Wahyu Nur Achmadin (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
This study evaluates the effects of ECU remapping, ignition system adjustments, and air-fuel ratio (AFR) modifications on engine performance and emission characteristics. Tests were conducted over engine speeds ranging from 4000 to 9000 RPM with different configurations: ECU, ignition system, and AFR adjustments. Results indicate that AFR remapping combined with fuel system tuning enhances torque and power at mid-range RPM, reaching a maximum torque of 12.98 N·m and power of 12.25 HP. ECU and ignition modifications increased CO and HC emissions, whereas AFR optimization through the fuel system reduced CO and improved Lambda toward stoichiometric balance. These findings highlight the importance of balancing performance improvement with emission control.